Health at work and coping with stress of prison officers - Sygit–Kowalkowska, Ewa; Weber-Rajek, Magdalena; Szrajda, Justyna; Kraszkiewicz, Krzysztof (Journal of Education, Health and Sport, 2017)
Background The aim of the study was to assess the state of mental and physical health and the expressed strategies for coping with stress of prison officers which are a group that is relatively unknown and seldom subjected to the tests. Among the coping strategies, the authors also identified those that were predictors of mental and physical well-being at work men working professionally in penitentiary institutions. Material and Methods The sample consisted of 90 prison officers working in the security department who are in direct contact with inmates. The control group consisted of 85 men working in services and trade in the Kujawsko-Pomorskie Voivodeship (Poland), chosen by the authors as a result of intentional selection. The study used the following tools: "Psychosocial Working Conditions" Questionnaire by R. Cieślak, M. Widerszal – Bazyl, Mini-COPE Questionnaire by C.S. Carver, adapted to Poland by Z. Juczyński and N. Ogińska-Bulik. Socio-demographic data were also collected. The results were compared with a group of men working outside the uniformed services. Results In the group of prison officers, longer seniority was associated with a statistically significant deterioration of mental and physical well-being. Based on higher level of seeking support in stressful situations as well as a lower level of helplessness, one could predict a higher general level of physical and mental well-being. Conclusions Due to the character of the work and the risk of negative phenomena is important broad-based health promotion in this occupational group.